2013
DOI: 10.1073/pnas.1211287110
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxic radioactive Listeria at is a highly effective therapy against metastatic pancreatic cancer

Abstract: No significant improvement in therapy of pancreatic cancer has been reported over the last 25 y, underscoring the urgent need for new alternative therapies. Here, we coupled a radioisotope, 188 Rhenium, to an attenuated (at) live Listeria monocytogenes (Listeria at ) using Listeria-binding antibodies, thus creating a unique radioactive Listeria at (RL). We then demonstrated in a highly metastatic pancreatic mouse tumor model (Panc-02) that RL delivered radioactivity to the metastases and less abundantly to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
176
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(180 citation statements)
references
References 23 publications
4
176
0
Order By: Relevance
“…Quispe-Tintaya et al (6) suggest the following mechanisms of action for the unique therapeutic strategy (Fig. 1): Based on their results and previous publications (9-11), the authors hypothesize that direct cytotoxicity caused by 188 Re radiation, especially in highly proliferating metastases, resulted in cancer cell death.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Quispe-Tintaya et al (6) suggest the following mechanisms of action for the unique therapeutic strategy (Fig. 1): Based on their results and previous publications (9-11), the authors hypothesize that direct cytotoxicity caused by 188 Re radiation, especially in highly proliferating metastases, resulted in cancer cell death.…”
mentioning
confidence: 99%
“…Quispe-Tintaya et al, as reported in PNAS, have taken a major next step in this emerging field of biological therapy (6). The authors report a unique combinatorial strategy against cancer using radiolabeled antibodies bound to tumor-colonizing bacteria, thereby enhancing therapeutic efficacy in a model of metastatic pancreatic cancer in mice.…”
mentioning
confidence: 99%
See 3 more Smart Citations